2019
DOI: 10.7717/peerj.6206
|View full text |Cite
|
Sign up to set email alerts
|

Local fishermen’s perceptions of the usefulness of artificial reef ecosystem services in Portugal

Abstract: Proponents of artificial reef (AR) deployment are often motivated by the usefulness of such structures. The usefulness of ARs is related to their capability of providing ecosystem services/additional functions. We present two distinct Portuguese AR case studies: (1) The Nazaré reef off the central coast of Portugal and (2) the Oura reef off the Algarve coast. Semi-structured interviews were conducted with local fishermen in the fishing towns of Nazaré and Quarteira pre-and post-AR deployment. The main focus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 85 publications
0
11
0
1
Order By: Relevance
“…In fact, several authors have studied the way in which objects are cast into the sea to improve fish habitats [27][28][29]. Old fishing vessels deliberately sunk can also serve to provide further points of interest for recreational scuba diving [30,31]. In this line, Devault et al [32] consider using deliberately sunk vessels to create ARs as an alternative to their land-based recycling.…”
Section: The Role Of Green Artificial Reefs In the Circular Economymentioning
confidence: 99%
“…In fact, several authors have studied the way in which objects are cast into the sea to improve fish habitats [27][28][29]. Old fishing vessels deliberately sunk can also serve to provide further points of interest for recreational scuba diving [30,31]. In this line, Devault et al [32] consider using deliberately sunk vessels to create ARs as an alternative to their land-based recycling.…”
Section: The Role Of Green Artificial Reefs In the Circular Economymentioning
confidence: 99%
“…It is expected that the method does not only introduce a lower cost but also a better option for the environment. The Practical Guidelines for Artificial Reefs in the Mediterranean and the Black Sea from the United Nation's Food and Agriculture Organization FAO will then be referred [12]. The detained boats can be supplied by LKIM which they are more than ready to dispose or get rid-off.…”
Section: Figure 6 Possible Placement Of the Lrwifi Towersmentioning
confidence: 99%
“…There are many studies have demonstrated the usefulness of artificial reefs in biodiversity enhancement [10,11]. Some others have provided insight into ARs in the provision of various ecosystem services [12][13][14]. Activities such as scientific diving make it possible to demonstrate this type of improvement [15].…”
Section: Introductionmentioning
confidence: 99%